Manajemen Sarana dan Prasarana Pendidikan - Muhammad Ibnu Faruk Fauzi (STAI Sangatta Kutai Timur, 2020)
Education is a conscious and deliberate effort to create an atmosphere of learning and the learning process so that learners are actively developing the potential for him to have the spiritual power of religion, self-control, personality, intelligence, character, and skills needed him, the community, the nation and the State (Law National education No. 20 Th. 2003) on quality improvement is one of the pillars of the development of education in Indonesia. School is a system that has a purpose. In connection with efforts to achieve these goals, problems can arise. These problems can be grouped in accordance with the administrative tasks that are the responsibility of the school administrator, so it is the substance of the administrative duties of school heads as the administrator. Among these are tasks grouped into the substance of school supplies. With facilities and infrastructure that meet expected output from there to reach the initial goal of an educational institution itself, but to infrastructure education was adequate and relevant to the needs of the perluhnya Further investigations on the Management of Infrastructures, so that the vision and mission of the school will be achieved in accordance with the initial planning.